Clinical Evaluation of Intrabony Defects in Localized Aggressive Periodontitis Patients with and without Bioglass- An In-vivo Study - Satyanarayana, KV; Anuradha, BR; Srikanth, G; Chandra, P Mohan; Anupama, T; Durga, M Prasad (Kathmandu University Medical Journal, 2012)
Background Aggressive periodontitis is a specific type of periodontitis with clearly identifiable clinical characteristics such as “rapid attachment loss, bone destruction” and “familial aggregation”. Regeneration of mineralized tissues affected by aggressive periodontitis comprises a major scientific and clinical challenge. In recent years some evidence has been provided that bioactive glass is also capable of supporting the regenerative healing of periodontal lesions. Objective The aim of this clinical and radiological prospective study was to evaluate the efficacy of bioactive glass in the treatment of intra-bony defects in patients with localized aggressive periodontitis. Methods Twelve localized aggressive periodontitis patients with bilaterally located three-walled intra-bony defect depth ? 2 mm, preoperative probing depths ? 5 mm were randomly treated either with the bioactive glass or without the bioactive glass. The clinical parameters plaque index, gingival index, probing depth, gingival recession, clinical attachment level, and mobility were recorded prior to surgery as well as 12 months after surgery. Intraoral radiographs were digitized to evaluate the bone defect depth at baseline and 12 months after the surgery. Results After 12 months, a reduction in probing depth of 3.92 + 0.313 mm (P